(untitled) (Physical Education, Health and Social Sciences, 2026)
Pakistan is also facing high deforestation and climate risks, as it has a forest cover of less than 5%. Climate-smart forestry can help Pakistan to increase its carbon sinks, promote ecosystem restoration, and achieve economic growth through sustainable practices such as afforestation and REDD+. This policy brief discusses the issues, current policies, results, and recommends a green economy policy through an integrated policy approach to achieve 10-15% emission cuts by 2030 through targeted investments.